Effect of phosphorus management on yield, nutrient uptake by sesame (Sesamum indicum L.) and soil fertility under irrigated conditions of southern Haryana: EFFECT OF PHOSPHORUS ON YIELD, N UPTAKE AND SOIL FERTILITY OF SOUTHERN HARYANA - M K JAT; R SINGH; P K YADAV; ABHA TIKKOO; R S DADARWAL; J S YADAV (Journal of Oilseeds Research, 2020)
Field experiments were carried out during kharif season from 2015 to 2017 in randomized block design with three replications. There were five graded levels of phosphorus application viz., 0, 10, 20, 30, and 40 P2O5 kg/ha. Seed yield increased significantly with application of 20 P2O5 kg/ha. The increase in mean seed and stalk yield was 6.1, 13.2, 15.4 and 18.0% and 6.2, 14.3, 17.6 and 19.9% due to application of 0, 10, 20, 30 and 40 P2O5 kg/ha, respectively over control. Application of 20 kg P2O5/ha recorded significantly higher protein content (21.10%) and oil content (48.69%) in seed, which was statistically at par with 30 and 40 kg P2O5/ha. P use efficiency varied from 14.1 to 20.3% and was maximum (20.3%) with application of 20 P2O5 kg/ha. The mean post-harvest available P status was 9.9, 11.3, 12.7, 13.5 and 14.1 kg/ha at 0, 10, 20, 30 and 40 P2O5 kg/ha, respectively. Based on the results of research experiment, on farm trials (OFT) were conducted on the farmers’ fields with two treatments, control and 20 kg P2O5/ha. The result of OFT revealed that the application of 20 kg P2O5/ha increased the seed yield ofsesame by 11.71 per cent over control. Application of 20 P2O5 kg/ha was optimum for the cultivation of sesame crop in coarse textured medium phosphorus status soils under irrigated condition of south-west Haryana